2019
DOI: 10.1007/s12602-019-09587-w
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum Strains Isolated from Polish Regional Cheeses Exhibit Anti-Staphylococcal Activity and Selected Probiotic Properties

Abstract: Twenty-nine Lactobacillus plantarum strains isolated from different types of Polish regional cheeses (Oscypek and Korycinski) were assessed for selected probiotic properties and anti-staphylococcal activity. Most of the tested L. plantarum strains were considered safe. Whole bacterial cultures (WBC) and cell-free supernatants (CFSs) of L. plantarum strains inhibited growth of Staphylococcus aureus (average inhibition growth zones were 2.8 mm ± 1.2 and 2.8 mm ± 1.1 respectively). Moreover, almost all neutralize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Thus, these findings are in agreement with those reported by other authors, who also attested that after neutralizing the pH of LAB supernatant, there was an absence or reduction in the inhibitory activity against indicator pathogens (Pisano et al, 2014;dos Santos et al, 2015;Sornplang and Piyadeatsoontorn, 2016;Ołdak et al, 2017;Partovi et al, 2019). Such behavior can be explained by other mechanisms of inhibition related to LAB in addition to bacteriocin production, such as competition for substrates and decreased pH levels by organic acid production (e.g., lactic, formic, propionic, and acetic acids; Favaro et al, 2015;Ołdak et al, 2019). So, these data demonstrate that antagonistic activity shown against the indicator pathogens allows the application of studied LAB isolates as biopreservatives in the production of dairy foods, increasing their shelf life.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, these findings are in agreement with those reported by other authors, who also attested that after neutralizing the pH of LAB supernatant, there was an absence or reduction in the inhibitory activity against indicator pathogens (Pisano et al, 2014;dos Santos et al, 2015;Sornplang and Piyadeatsoontorn, 2016;Ołdak et al, 2017;Partovi et al, 2019). Such behavior can be explained by other mechanisms of inhibition related to LAB in addition to bacteriocin production, such as competition for substrates and decreased pH levels by organic acid production (e.g., lactic, formic, propionic, and acetic acids; Favaro et al, 2015;Ołdak et al, 2019). So, these data demonstrate that antagonistic activity shown against the indicator pathogens allows the application of studied LAB isolates as biopreservatives in the production of dairy foods, increasing their shelf life.…”
Section: Discussionsupporting
confidence: 93%
“…Despite their transient occurrence in the GI tract, dairy LAB can nonetheless influence the resident microbiome and exert host-specific health benefits [14]. In addition to human GIT, potential probiotic candidates have been recently isolated from different kinds of fermented milks [172][173][174][175][176], cheeses [177][178][179][180][181][182], and kefir. Even if rigorous guidelines define when a single microbe or microbial consortia can be properly qualified as probiotic [183], these studies provided the basis for the development of new functional foods and defined a cohort of strains which will be in future employed as therapeutic adjuvants for in vivo studies.…”
Section: The Renaissance Of Interest Towards Artisanal Fdfmentioning
confidence: 99%
“…These findings extended the knowledge concerning antimicrobial applications of CFSs from L. plantarum strains. In fact, several studies reported the potential of L. plantarum cell-free supernatants against foodborne pathogens (e.g., Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus [ 45 , 46 , 47 ]), other human pathogens (e.g., oral Candida species [ 48 ]), microbes producers of toxic compounds in foods (e.g., fumonisin producing Fusarium proliferatum , amine-positive bacteria [ 49 , 50 ]), spoilage fungi (e.g., Aspergillus niger , Aspergillus flavus , and Fusarium oxysporum [ 51 , 52 ]), and plant pathogens (e.g., Pseudomonas syringae pv. actinidiae , Xanthomonas arboricola pv.…”
Section: Resultsmentioning
confidence: 99%